Taking Cultural Heritage Seriously. Sociological Theory, Emotions and Human Rights. Niklas Luhmann in Memoriam - Magnolo, Stefano; Galán-Pérez, Ana (Italian Sociological Review, 2025)
This study focuses on the communication of intangible cultural heritage (ICH), defined to include the scientific production of researchers across both the hard sciences and the humanistic and social realms. Considering museums as institutions of memory undergoing transformation due to new technologies, we analyse institutional definitions of ICH and museums from a global perspective. We also examine the languages, technologies, and contexts suitable for communicating ICH in museums. Our analysis is based on an empirical study conducted in Germany, exploring the use of digital technologies to transmit and valorize ICH through museum initiatives, with a focus on the emotional aspect. In addition to its theoretical background, this study reflects on the roles of law, human rights, and emotions in defining cultural identity, concluding with a provocative proposal on enhancing cultural communication.